A study of symmetric points in Banach spaces. Issue 5 (24th March 2022) - Sain, Debmalya; Roy, Saikat; Bagchi, Satya; Balestro, Vitor
ABSTRACT: We completely characterize the left-symmetric points, the right-symmetric points, and the symmetric points in the sense of Birkhoff-James, in a Banach space. We obtain a complete characterization of the left-symmetric (right-symmetric) points in the infinity sum of two Banach spaces, in terms of the left-symmetric (right-symmetric) points of the constituent spaces. As an application of this characterization, we explicitly identify the left-symmetric (right-symmetric) points of some well-known three-dimensional polyhedral Banach spaces.